Study of Mistletoe in Joben Resort Forest Mount Rinjani Lombok - Wahyuni Dwi Fikriani; Tri Mulyaningsih; Evy Aryanti (Biosaintifika: Journal of Biology & Biology Education, 2017)
Mistletoes are one group of hemiparasite plants, including the Lorantaceae family that have potential as medicinal. These hemiparasite plants can attack flowering plant (Magnoliophyta) and non-floweing plant (Pinophyta), especially on the main stems, branches and twigs. The objective of this research is to identify the species of mistletoe and its hosts, make identification key, descriptions, and to make a distribution map of mistletoe in Joben Resort forest south of Mount Rinjani Lombok. This study is descriptive explorative research with three kinds of collecting sample methods i.e exploration, continous strip sampling, and delenation method. The research found five species of mistletoes are included in three genera i.e Amyema cuernosensis, Amyema enneantha, Amyema tristis, Macrosolen retusus and Scurrula artropurpurea. These five kinds of mistletoe are associated with 23 hosts species of plants, 18 genera from 13 families. The most favorite host of these mistletoes is Ficus septica, and the most agresive mistletoe is Scurrula artropurpurea. The important finding of the research is finding new species or new record of mistletoes. The benefit of these new record or new species is providing new material of new medicinal for treating some diseases such as various cancers.